Bayesian modeling of HFC production pipeline suggests growth in unreported CFC by-product and feedstock production - Stephen Bourguet; Megan Lickley (Nature Communications)
Abstract Observationally-derived emissions of ozone depleting substances must be scrutinized to maintain the progress made by the Montreal Protocol in protecting the stratospheric ozone layer. Recent observations of three chlorofluorocarbons (CFCs), CFC-113, CFC-114, and CFC-115, suggest that emissions of these compounds have not decreased as expected given global reporting of their production. These emissions have been associated with hydrofluorocarbon (HFC) production, which can require CFCs as feedstocks or generate CFCs as by-products, yet emissions from these pathways have not been rigorously quantified. Here, we develop a Bayesian framework to jointly infer emissions of CFC-113, CFC-114, and CFC-115 during HFC-134a and HFC-125 production. We estimate that feedstock emissions from HFC-134a production accounted for 90% (82–94%) and 65% (47–77%) of CFC-113 and CFC-114 emissions, respectively, from 2015–2019, while by-product emissions during HFC-125 production accounted for 81% (68–92%) of CFC-115 emissions. Our results suggest that unreported feedstock production in low- to middle-income countries may explain the unexpected emissions of CFC-113 and CFC-114, although uncertainties within chemical manufacturing processes call for further investigation and industry transparency. This work motivates tightened feedstock regulations and adds a reduction in CFC emissions to the benefits of the HFC phasedowns scheduled by the Kigali Amendment.